(untitled) (Third Sector Social Economic Review, 2022)
Economic integration, in other words, liberalization of trade, can cause changes in the spatial distribution of economic activities in countries. The New Theory of Economic Geography provides an important analytical framework for revealing the spatial dimension of trade liberalization. The New Economic Geography theory explains the answer to the question of why economic activities choose certain places as settlement areas, with the interaction between centripetal forces and opposing forces called centrifugal forces. The center-periphery model is accepted as the basic model for the New Economic Geography Theory. In the study, main aim is to evaluate the results of theoretical/empirical studies investigating the effects of economic integration/trade liberalization on the positioning of economic activities within the framework of the center-periphery model, which is the basic model of the New Economic Geography Theory. It can be concluded that the results obtained in studies examining within the framework of the center-periphery model, which is the basic model of the New Economic Geography Theory, can be gathered into two groups with opposite results. While some of the aforementioned studies reveal that economic integration encourages the manufacturing industry to disperse within the country, another part of the studies demonstrates that economic integration causes an increase in spatial density. It is contemplated that the sensitive relations between centripetal and centrifugal forces play an important role in the emergence of these contradictory results obtained in this context. Therefore, it is considered that changing the assumptions will affect the results to be obtained.